2007
DOI: 10.1016/j.otohns.2006.11.036
|View full text |Cite
|
Sign up to set email alerts
|

Idiopathic temporal bone encephaloceles in the obese patient

Abstract: TBE is associated with morbid obesity in our population and should be considered in the differential diagnosis when evaluating mastoid and middle ear disease in the morbidly obese.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
63
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(66 citation statements)
references
References 17 publications
3
63
0
Order By: Relevance
“…8,22,24,26,27 We found that the mean BMI and the prevalence of empty sella syndrome were higher in patients with spontaneous lesions than in those with nonspontaneous lesions; however, these differences did not reach statistical significance. Our data reveal a female preponderance among patients with spontaneous CSFFs, similar to that observed among patients with idiopathic intracranial hypertension syndrome.…”
mentioning
confidence: 56%
See 1 more Smart Citation
“…8,22,24,26,27 We found that the mean BMI and the prevalence of empty sella syndrome were higher in patients with spontaneous lesions than in those with nonspontaneous lesions; however, these differences did not reach statistical significance. Our data reveal a female preponderance among patients with spontaneous CSFFs, similar to that observed among patients with idiopathic intracranial hypertension syndrome.…”
mentioning
confidence: 56%
“…It has been hypothesized that elevated intracranial pressure may contribute to progression of temporal bone encephaloceles and CSFF, and an increased risk of recurrence following repair. 1,8,22,26 Given the rarity of the studied conditions, few large series exist in the literature, and optimal surgical management remains controversial. 7,14,15,20,21 Treatment options include the transmastoid approach with tegmen repair or tympanomastoid obliteration, subtemporal middle fossa craniotomy, or a combined mastoid-middle fossa approach.…”
mentioning
confidence: 99%
“…1 Recently there has been growing evidence that obesity is also a risk factor for development of spontaneous temporal bone CSF leaks. 6,12,17,21 In contrast, little has been written regarding the possible association between obesity and the occurrence of a CSF leak following VS surgery. 8,14 Diaz Anadon et al studied 170 patients who had undergone surgery for tumors in the cerebellopontine angle (163 of whom had a VS) and found no relationship between CSF leaks and BMI.…”
Section: Discussion Elevated Bmi As a Risk Factor For A Csf Leakmentioning
confidence: 99%
“…This has been noted by several authors, particularly in patients with spontaneous CSF leaks and idiopathic intracranial hypertension. 7,12,17,21,22 It has been demonstrated that intraabdominal pressure in obese patients is elevated and that this in turn translates into higher intrathoracic and cardiac filling pressures, thus decreasing venous return from the brain and ultimately increasing ICP. 22 Some have postulated that the increased amount of estrogen produced by adipose tissue in obese patients may play a role in the development of elevated ICP-abnormally high levels of estrogen have been found in the CSF of obese patients with idiopathic intracranial hypertension.…”
Section: Discussion Elevated Bmi As a Risk Factor For A Csf Leakmentioning
confidence: 99%
“…6,7,[10][11][12]15 As the middle fossa cranial base develops progressively enlarging defects, CSF pulsations contribute to dehiscence and can lead to meningoencephalocele development and eventual dural disruption. 4,8,12,16 This sequence of events results in effusions in the middle ear and mastoid air cells that can manifest as CSF fistulas, through a disrupted tympanic membrane or via the eustachian tube. [1][2][3]5,11,12,15 Given that intracranial hypertension has been implicated as a significant factor in temporal encephalocele formation, 7,[10][11][12]15 we hoped to clarify this correlation by reviewing a series of tegmen defects repaired surgically and the associated ICP measurements in these patients.…”
mentioning
confidence: 99%